Effect of long-term application of fertilizers on agrochemical parameters of typical chernozem and grain quality of winter wheat - Zaryshniak, A. S.; Lisovyi, M. V.; Nikonenko, V. M.; Slidenko О. I. (AgroChemistry and Soil Science, 2023)
The aim of the article is to present the results of analytical research on the evaluation of changes in the parameters of the properties of typical chernozem in a stationary field experiment under the influence of 28 years of application of various types and combinations of mineral fertilizers on two agrophones in a crop rotation. The experiment established in 1990 on a typical heavy loam chernozem (Haplic Chernozem) in the experimental farm "Hrakivske” which belongs to the NSC "Institute for Soil Science and Agrochemistry Research" named after O. N. Sokolovsky, in the Chuguyiv district of the Kharkiv region. The aim was to conduct agroecological monitoring in conditions of intensive agriculture to establish the permissible level of load of intensive chemicalization on physical, chemical, and biological soil processes. In the soil samples taken in 2019 from the 0-30 cm layer, the changes that occurred after long-term application of fertilizer in the pH of the soil solution and the content of the following soil components were determined: humus; mineral compounds of nitrogen; nitrate nitrogen; ammonium nitrogen; mobile phosphorus compounds; mobile compounds of potassium. The quality of winter wheat grain determined by the gluten content. Seven variants of the experiment with different fertilizer combinations and the control variant (without fertilizers) placed on two agrophones: natural (only mineral fertilizers applied) and after-effect of manure (mineral fertilizers and manure applied). The results of the research in 2019 compared with the initial state of the soil in 1990 separately at each site, thus revealing changes in the parameters of the agrochemical characteristics of the soil under the influence of different types of fertilizers. Common conclusion. In the Left-bank high Forest-Steppe of Ukraine, the long-term (28 years) application of mineral fertilizers in the natural agrophone has a negative effect on the reaction of the soil solution and the content of total humus, but has a positive effect on the accumulation of mobile compounds of nitrogen, phosphorus, and potassium in the soil. The negative effect of mineral fertilizers on the soil properties manifested to a lesser extent after the application of manure. The application of nitrogen and phosphorus fertilizers in the norms of N60P120 provides a gluten content in winter wheat grains at the level of 25 %, which meets the regulatory requirements of the second class of group A.